Case Report: A rare presentation of rapidly progressive moyamoya disease refractory to unilateral surgical revascularization - Leach, Daniel Friel; Margam S, Srivikram; Gustin, Aaron; Gustin, Paul J.; Jajeh, Mohamad N.; Chavis, Yhana C.; Walker, Kristin V.; Bentley, Joshua S. (Frontiers in Surgery, 2024)
Moyamoya disease (MMD) is a chronic, occlusive cerebrovasculopathy typified by progressive steno-occlusive disease of the intracranial internal carotid arteries (ICAs) and their proximal branches. Moyamoya syndrome (MMS) categorizes patients with characteristic MMD plus associated conditions. As such, the most usual presentations are those that occur with cerebral ischemia, specifically transient ischemic attack, acute ischemic stroke, and seizures. Hemorrhagic stroke, headaches, and migraines can also occur secondary to the compensatory growth of fragile collateral vessels propagated by chronic cerebral ischemia. While the pathophysiology of MMD is unknown, there remain numerous clinical associations including radiation therapy to the brain, inherited genetic syndromes, hematologic disorders, and autoimmune conditions. We describe the case of a 31-year-old woman who presented with recurrent ischemic cerebral infarcts secondary to rapidly progressive, bilateral MMD despite undergoing early unilateral surgical revascularization with direct arterial bypass. She had numerous metabolic conditions and rapidly decompensated, ultimately passing away despite intensive and aggressive interventions. The present case highlights that progression of moyamoya disease to bilateral involvement can occur very rapidly, within a mere 6 weeks, a phenomenon which has not been documented in the literature to our knowledge.